PENEGAKAN HUKUM PERSAINGAN USAHA DI INDONESIA MELALUI HARMONISASI PUBLIC ENFORCEMENT DAN PRIVATE ENFORCEMENT [Competition Law Enforcement in Indonesia through the Harmonization of Public Enforcement and Private Enforcement] - Carissa Christybella Wijaya; Micheline Hendrito; Monica Patricia Aripratama; Udin Silalahi (Law Review, 2021)
KPPU (Commission for the Supervision of Business Competition) as the authority for business competition law in Indonesia still has many shortcomings. This is related to the KPPU’s failure to accommodate compensation payments to victims of business competition law violations. This can happen because Indonesia has only provided room for public enforcement to be implemented. In public enforcement, compensation payments are not paid directly to consumers who have suffered losses but instead come into the state treasury. This article discusses the compensation mechanism that should be received by victims of competition law violations through private enforcement, which is a mechanism for enforcing competition law by using the regulations of the Competition Law in civil courts to demand compensation. This research was conducted with the aim of creating a healthy business competition climate through the enforcement of private enforcement in Indonesia by implementing harmonization between public and private enforcement. In this article, the Authors used normative juridical method and refers to statutory and comparative approaches. The research method used is juridical normative with a statute approach, a case approach, and a comparative legal approach. The results and conclusions of this study are that the KPPU's failure to provide compensation for compensation to victims of business competition violations encourages the need to implement private enforcement in Indonesia which is harmonized with the previous mechanism, namely public enforcement.Bahasa Indonesia Abstrak: KPPU (Komisi Pengawas Persaingan Usaha) sebagai lembaga otoritas dalam hukum persaingan usaha di Indonesia masih memiliki banyak kekurangan. Salah satunya terkait dengan kegagalan KPPU dalam mengakomodir pembayaran ganti rugi kepada korban pelanggaran hukum persaingan usaha. Hal ini dapat terjadi karena selama ini Indonesia hanya memberikan ruang bagi public enforcement untuk diterapkan. Dalam public enforcement, pembayaran ganti rugi tidak dibayarkan langsung kepada konsumen yang dirugikan melainkan masuk ke dalam kas negara. Oleh sebab itu, terdapat sebuah urgensi untuk mengalihfungsikan fungsi kompensasi dari KPPU kepada pelaku usaha melalui private enforcement, yaitu sebuah mekanisme penegakan hukum persaingan usaha dengan menggunakan regulasi UU Persaingan Usaha di peradilan perdata untuk menuntut ganti rugi. Penelitian ini dilakukan dengan tujuan untuk menciptakan iklim persaingan usaha yang sehat melalui ditegakkannya private enforcement di Indonesia dengan menerapkan harmonisasi antara public enforcement dan private enforcement. Metode penelitian yang digunakan, yaitu yuridis normatif dengan pendekatan undang-undang, pendekatan kasus, dan pendekatan komparatif hukum. Hasil dan kesimpulan dari penelitian ini adalah kegagalan KPPU dalam memberikan kompensasi ganti rugi kepada korban pelanggaran persaingan usaha mendorong perlu diterapkannya private enforcement di Indonesia yang diharmonisasikan dengan mekanisme sebelumnya, yaitu public enforcement.